A method of landfill leachate management using internet of things for sustainable smart city development - Gopikumar, S.; Raja, S.; Robinson, Y. Harold; Shanmuganathan, Vimal; Chang, Hangbae; Rho, Seungmin (Sustainable cities and society, 2021)
An urban local body of our country has planned to establish innovative and affordable method of treating solid waste offsite. Current manual waste segregation method is still a challenge for the environmental sustainability and considering the fact a mechanical waste segregator is designed which can identify the type of waste and separate them using Arduino microcontroller. The separated solid wastes are subjected to landfill and a review on landfill leachate management practice is presented in this paper. Then an enhanced Sequential Leach Bed–HUASB Reactor design is proposed for leachate treatment. The fabricated pilot scale model was functioning in the mesophilic state with pretreated solid waste as feed for ten different organic loading. The routine and real time monitoring of process control is based on plasma that depends on remote and onsite control. The materialization of devices is based on the Internet of Things (IoT) cloud, which is observed to be the emerging trend. By captivating the field data the devices are related to the process of mathematical calculation that plays significant role in transforming to the objects and are used to scrutinize turbidity, suspended solids, dissolved oxygen and COD using sensors, thereby managing the leachate for making Sustainable smart city development.